Legume introduction increases soil organic carbon in grassland via regulation of microbial metabolism regardless of phosphorus fertilization - Meiqi Guo; Tongtian Guo; Gaowen Yang; Nan Liu; Jiqiong Zhou; Yingjun Zhang (Geoderma)
Introducing legumes into grasslands can enhance soil organic carbon (SOC) storage, but high phosphorus (P) requirement of legume nitrogen (N) fixation may accelerate soil P depletion. As a result, P fertilizers are often applied to improve legume performance. However, the effects of legume introduction and P availability on SOC storage in grasslands remain poorly understood. In this study, we investigated how legume introduction and P fertilization influence SOC physical fractions and associated microbial metabolic activities, based on a ten-year field experiment. Our results showed that legume introduction increased mineral-associated organic carbon (MAOC) by 7.4 % and total SOC by 5.7 % compared to grasslands without legume introduction. This enhancement can be attributed to the improved soil substrate quality (lower carbon to nitrogen ratio) and enhanced microbial carbon (C) limitation (relative microbial nutrient limitation calculated using vector analysis based on ecoenzymatic stoichiometric theory models), which led to higher microbial carbon use efficiency (CUE) and lower microbial metabolic quotient (qCO2). Phosphorus fertilization reduced microbial biomass and qCO2 by increasing microbial C limitation, thereby leading to a 9.3 % increase in particulate organic carbon (POC); however, it did not affect SOC compared to no P fertilization. Moreover, the positive effect of P on POC was observed only when legume was not introduced, indicating legume introduction weakened this positive effect. In conclusion, introducing legumes to natural grasslands can enhance long-term SOC stabilization and storage by stimulating microbial metabolic activity, offering a sustainable strategy to improve soil fertility and agricultural productivity without the need for P fertilization.